THE RELEVANCE OF THE CONCEPT OF THE KHILAFAH ECONOMY IN FACING THE INDONESIAN ECONOMIC CRISIS ACCORDING TO UMER CHAPRA - Arief, Suyoto; Izdihar, Nadia Ingrida (KOMITMEN: Jurnal Ilmiah Manajemen, 2025)
An economic crisis is a complex phenomenon that reflects the occurrence of significant disruption in the economic mechanism of a country or region, which has the potential to cause widespread impacts both socially and politically. Umer Chapra argues that the concept of the Khilafah is the foundation of Islamic economics that emphasizes social responsibility, justice, and collective welfare. So the purpose of this study is to determine the relevance of the Khilafah economy in dealing with the economic crisis in Indonesia. This study uses a descriptive qualitative research method with library research techniques. The results of this study are the relevance of the wealth distribution paradigm offered by the Khilafah, through the practice of zakat, sadaqah, and waqf, then, the usury-free financial system recommended in the Khilafah economy is very relevant to implemented in Indonesia. In addition, the role of the government in maintaining social welfare is also a crucial point in implementing the Khilafah economy. Finally, the values of social solidarity contained in the concept of the Khilafah can strengthen the economic resilience of society.